Australia and Brazil in the nuclear hierarchical order: divergent strategies regarding the nuclear weapons non-proliferation regime and their nuclear powered submarine program - Guimarães, Victoria Viana Souza [UNESP] (2025)
This research examines the reasons that led Brazil and Australia, both non-nuclear-weapon states (NNWS) pursuing nuclear-powered submarines (SSNs), to follow divergent paths in their SSN programs. The central hypothesis is that Brazil prioritizes nuclear autonomy as a strategic principle, aligning with its broader nuclear policy, while Australia’s approach is driven by its pursuit of middle-power status, emphasizing alliance-building and external support. Using a comparative method, this study analyzes the evolution of Brazil’s and Australia’s nuclear policies from 1945 to 2024, assessing their domestic, regional, and international contexts. The findings reveal that Brazil's SSN development stems from its longstanding emphasis on technological autonomy, reflected in its nuclear cooperation with Argentina and its critical stance on the Nuclear Weapons Non-Proliferation Regime (NWNPR). In contrast, Australia's SSN pursuit is deeply embedded in alliances with nuclear-armed states, notably through the AUKUS partnership, highlighting its reliance on external security commitments. The study concludes that both nations' SSN trajectories reflect broader strategic frameworks—Brazil’s pursuit of autonomy and Australia’s pursuit of middle power status—shaped by historical, geopolitical, and institutional factors. These findings contribute to understanding how NNWS navigate nuclear technology within the constraints of the NWNPR.